Ethical requirements for the legal profession in the context of implementing the current undergraduate law curriculum standards in Vietnam - Chu Binh Minh (Journal of State Management, 2025)
The legal profession is closely associated with the legal status of individuals. Therefore, professionalcompetence, particularly legal ethics with its core standards in the current context - such as honesty, integrity, respect for the rule of law, protection of justice and human rights, avoidance of conflicts of interest, confidentiality, social responsibility, and accountability - has become increasingly essential. Accordingly, ethical qualities and codes of conduct in legal practice are not only objective requirements to meet the rising expectations of society toward legal professionals but also demand that undergraduate law training programs comply with established curriculum standards. This ensures behavioral orientation, preservation of professional identity, and better service to the People and the nation, while simultaneously safeguarding justice and strengthening the rule of law in the new context.